Proposed draft law for public libraries in Egypt - Mostafa Hossam El-Din (Cybrarians Journal, 2025)
This proposed draft law for public libraries in Egypt addresses the urgent need for a legislative framework to govern public libraries in Egypt. Despite the recent growth in the number and reach of public libraries, there remains a significant legislative vacuum that hinders their optimal operation, equitable distribution, and integration into national development efforts.